Preparation method and application of honeycomb layered coated synergistic multi-site doped sodium ion battery positive electrode material
Patent Information
- Application Number
- CN202611040597.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]针对现有技术中存在的钠离子电池层状氧化物正极材料空气稳定性不足、动力学缓慢以及结构不稳定等问题,本发明提供了一种蜂窝层状包覆协同多位点掺杂的钠离子电池正极材料及其制备方法和应用;本发明通过简单的一步法将结构相似的蜂窝状A3B2CO6包覆在NaxNiaFebMn1-a-bO2-yMy材料上,阻挡空气和电解液的侵蚀,同时A、B、C、M原子分别取代Na、TM、O位点,多位点掺杂改变了原子配位环境,不仅能降低钠离子扩散能垒,还能有效铆钉过渡金属和阴离子,能够有效提高稳定层状结构,提高正极材料的存储性、安全性和实用性;所述正极材料的制备工艺流程具有原料易得、制备方法简单、可控性高等优点,具备良好的应用前景
(1)本发明所述蜂窝层状包覆协同多位点掺杂的钠离子电池正极材料的改性材料A3B2CO6(A=Na、Li、Cu、Ag,B=Zn、Mg,C=Sb、Bi)是一种结构稳定的P2相层状钠离子固体电解质材料,其室温离子电导率(~1.1mS/cm)基本与NASICON电解质水平相当。并且P2相A3B2CO6具有结构稳定和离子电导率更高的优势;
Smart Images

Figure CN122992020A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery layered oxide cathode technology, specifically a method for preparing sodium-ion battery cathode material with honeycomb layered coating and synergistic multi-site doping and its application. Background Technology
[0002] In recent years, with the booming development of the new energy field, lithium resources can no longer meet the needs of large-scale energy storage in the future, and there is an urgent need for a new energy source to partially replace lithium-ion batteries. Sodium-ion batteries are considered a potential alternative to lithium-ion batteries due to their abundant resources, low cost, excellent low-temperature performance, and safety performance. However, this material currently suffers from problems such as insufficient air stability and poor structural reversibility. On the one hand, when storing this material in air, water and carbon dioxide in the air will attack the sodium layer and destroy the layered structure. On the other hand, during the operation of sodium-ion batteries, the large-radius sodium ions are prone to volume changes during repeated insertion and extraction, which exacerbates the migration and dissolution of transition metal ions and further triggers irreversible structural collapse such as oxygen loss. This leads to a significant reduction in material lifespan, increases storage costs, and hinders the commercialization of sodium-ion batteries. Summary of the Invention
[0003] To address the problems of insufficient air stability, slow kinetics, and structural instability in existing sodium-ion battery layered oxide cathode materials, this invention provides a honeycomb layered coated sodium-ion battery cathode material with synergistic multi-site doping, its preparation method, and its applications. This invention uses a simple one-step method to coat structurally similar honeycomb-shaped A3B2CO6 onto Na... x Ni a Fe b Mn 1-a-b O 2-y M y In terms of materials, it blocks the corrosion of air and electrolyte. At the same time, A, B, C, and M atoms replace Na, TM, and O sites respectively. Multi-site doping changes the atomic coordination environment, which not only reduces the sodium ion diffusion barrier but also effectively anchors the transition metal and anions, thereby effectively improving the stability of the layered structure and enhancing the storage performance, safety, and practicality of the cathode material. The preparation process of the cathode material has the advantages of readily available raw materials, simple preparation methods, and high controllability, and has good application prospects.
[0004] To achieve the above-mentioned technical objectives, the present invention employs the following technical means: A honeycomb layered coated sodium-ion battery cathode material with synergistic multi-site doping, characterized in that: the general chemical formula of the cathode material is Na. x-m B m (Ni a Fe b Mn 1-a-b) 1-n C n O 2-y M y @A3B2CO6; where 0.66≤x≤1, 0≤a≤0.33, 0≤b≤0.33, 0≤y≤0.1, 0.05≤m≤0.2, 0.05≤n≤0.2, and A3B2CO6 is a honeycomb layered structure. The surface is modified while the M element is combined to achieve multi-site regulation.
[0005] Preferably, M is selected from one of F, Cl, and S, and substitutes for oxygen ion sites to form strong TM-M bonds.
[0006] Preferably, in A3B2CO6, A is selected from one of Na, Li, Cu, and Ag; B is selected from one of Zn and Mg; and C is selected from one of Sb and Bi. The A3B2CO6 reacts with Na... x Ni a Fe b Mn 1-a-b O 2-y M y The mass ratio is (0.5% : 1) ~ (10% : 1).
[0007] This invention also provides a method for preparing the above-mentioned honeycomb layered coated sodium-ion battery cathode material with synergistic multi-site doping, specifically including the following steps: (1) Add sodium source, nickel source, iron source, manganese source, compound M, compound A, compound B and compound C into a ball mill jar, and then select appropriate solvent, rotation speed, ball milling time and solid ratio for ball milling and mixing. After ball milling, transfer to a vacuum drying oven for drying. (2) The obtained powder sample is pressed into a tablet under a certain pressure, and then sintered under a certain sintering atmosphere. After the reaction is completed, a sodium-ion battery cathode material with honeycomb layered coating and multi-site doping is obtained. Preferably, in step (1), the nickel source, manganese source, and iron source are one or more of their corresponding oxides, acetates, chlorides, nitrates, and sulfates; the sodium source includes one or more of Na2CO3, NaNO3, and NaHCO3. Preferably, the M compound includes one or more of acetate, ammonium salt, and sodium salt; Preferably, compound A includes one or more of oxides, nitrates, acetates, carbonates, and hydroxides; Preferably, compound B includes one or more of oxides, nitrates, acetates, carbonates, and hydroxides; Preferably, compound C includes one or more of oxides, nitrates, acetates, carbonates, and hydroxides; Preferably, the ball milling solvent includes any one of methanol, ethanol, propanol, and diethyl ether, and the solvent volume is 0-5 ml; Preferably, the mass ratio of milling beads to positive electrode material is 10-15:1; Preferably, the ball milling time is 6-15 h, the rotation speed is 400-800 r / min, and the vacuum drying time is 12-20 h; Preferably, in step (2), the sintering atmosphere is one or more of oxygen or air; the sintering method is one or more of microwave sintering, atmospheric pressure sintering, hot pressing sintering, reaction sintering, and self-sintering; and the pressing pressure is 0.5 MPa to 10 MPa. Preferably, the sintering time is 12-20 hours, the heating rate is 2-5 degrees Celsius per minute, and the sintering temperature is 850-950°C. o C; Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The modified material A3B2CO6 (A = Na, Li, Cu, Ag, B = Zn, Mg, C = Sb, Bi) of the honeycomb layered coated synergistic multi-site doped sodium-ion battery cathode material described in this invention is a structurally stable P2 phase layered sodium-ion solid electrolyte material, whose room temperature ionic conductivity (~1.1 mS / cm) is basically equivalent to that of NASICON electrolyte. Furthermore, P2 phase A3B2CO6 has the advantages of structural stability and higher ionic conductivity; (2) A3B2CO6 acts as a coating layer, which isolates the electrode material from direct contact with air / electrolyte, and inhibits the attack of H2O and CO2 on the Na layer and the side reactions with the electrolyte. (3) Because A3B2CO6 and Na x Ni a Fe b Mn 1-a-b O 2-y M y Having similar layered structures, the composite phase epitaxial interface formed by the two can effectively suppress the stress and volume expansion generated in the material during cycling, and improve the stability of the material structure and interface. (4) B atoms are inert and can support the layered structure during sodium ion insertion and extraction. At the same time, B atoms occupy the migration path of transition metal ions and inhibit the migration and dissolution of transition metal ions. A and C atoms have strong AO and CO bonds, which anchor the lattice oxygen. M atoms have high electronegativity and strong TM-M bonds stabilize the layered structure. Multi-site doping greatly stabilizes the layered structure, inhibits irreversible phase transitions during cycling, and extends the service life of the cathode material. (5) The raw materials of the present invention are readily available, the preparation is simple, the cost is low and the controllability is high. The resulting sodium-ion battery cathode material has good storage performance and long cycle life, which can significantly improve the practicality of cathode material and is suitable for mass production and application. Attached Figure Description
[0008] Figure 1 The images show the X-ray diffraction (XRD) patterns and partial magnified views of the materials prepared in the embodiments and comparative examples of this application.
[0009] Figure 2 The above are charge-discharge curves of the materials prepared in the embodiments and comparative examples of this application at a voltage range of 2.0 to 4.2 V and a rate of 0.1 C.
[0010] Figure 3 This is a comparison chart showing the cycling performance of the materials prepared in the embodiments and comparative examples of this application at a voltage range of 2.0 to 4.2 V and a 1 C rate. Implementation Cases
[0011] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0012] This invention provides a honeycomb-layered coated, multi-site doped sodium-ion battery layered oxide cathode material with the general chemical formula Na. x-m B m (Ni a Fe b Mn 1-a-b ) 1-n C n O 2-y M y @A3B2CO6, wherein A is at least one of Na, Li, Cu, and Ag, B is at least one of Zn and Mg, and C is at least one of Sb and Bi.
[0013] Surface modification strategies can not only improve air stability and reduce material loss during transportation, but also suppress interfacial side reactions between the electrode and electrolyte, inhibiting the formation of microcracks. Simultaneously, by modifying three sites on the cathode material, the structure of the transition metal layer can be stabilized, and the collapse of the sodium layer structure, the migration of the transition metal to the sodium layer, and the release of irreversible oxygen can be mitigated in the deep desodiumization state of the cathode material.
[0014] Specifically, in Na x-m B m (Ni a Fe b Mn 1-a-b ) 1-n C n O 2-y M y In the A3B2CO6 layered oxide cathode material, 0.66≤x≤1, 0≤a≤0.33, 0≤b≤0.33, 0≤y≤0.1, 0.05≤m≤0.2, and 0.05≤n≤0.2.
[0015] Specifically, in the layered oxide cathode material, element A can be at least one of Na, Li, Cu, and Ag, element B can be at least one of Zn and Mg, and element C can be at least one of Sb and Bi, and they can be combined in any molar ratio.
[0016] This invention also provides a method for preparing a three-point doped layered oxide cathode material, comprising the following steps: S1. Add sodium source, nickel source, iron source, manganese source, compound M, compound A, compound B, and compound C into a ball mill jar, and then use appropriate solvent, rotation speed, ball milling time, and solid-material ratio to ball mill and mix them. After ball milling, transfer them to a vacuum drying oven for drying. S2. The obtained powder sample is pressed into a tablet under a certain pressure, and then sintered under a certain sintering atmosphere. After the reaction is completed, a sodium-ion battery cathode material with honeycomb layered coating and multi-site doping is obtained. Preferably, in step (1), the nickel source, manganese source, and iron source are one or more of their corresponding oxides, acetates, chlorides, nitrates, and sulfates; the sodium source includes one or more of Na2CO3, NaNO3, and NaHCO3. S1.1, Compound M includes one or more of acetate, ammonium salt, and sodium salt; Compound A includes one or more of oxide, nitrate, acetate, carbonate, and hydroxide; Compound B includes one or more of oxide, nitrate, acetate, carbonate, and hydroxide; Compound C includes one or more of oxide, nitrate, acetate, carbonate, and hydroxide; the ball milling solvent includes any one of methanol, ethanol, propanol, and diethyl ether, and the solvent volume is 0-5 ml; the mass ratio of ball milling beads to positive electrode material is 5-10:1; the ball milling time is 6-15 h, the rotation speed is 400-800 r / min, and the vacuum drying time is 12-20 h; S1.2 The sintering atmosphere is one or more of oxygen or air; the sintering method is one or more of microwave sintering, atmospheric pressure sintering, hot pressing sintering, reaction sintering, and self-sintering; the pressing pressure is 0.5 MPa to 10 MPa; the sintering time is 12 to 20 hours, the heating rate is 2 to 5 degrees Celsius per minute, and the sintering temperature is 850 to 950 degrees Celsius. o C. Example 1
[0017] This embodiment 1 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, including the following steps: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0428 g of CuO, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of a tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2. The mixed sheet was placed in a sintering boat, which was then transferred to a tube furnace. Under an oxygen atmosphere, the tube furnace was heated from room temperature to 900°C at a rate of 3°C / min, and held at that temperature for 12 hours for sintering. The material was then cooled to 100°C in a muffle furnace at a rate of 3°C / min. The sintered material was then rapidly transferred to a glove box for storage, yielding Na. 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 F 0.05 @Cu3Zn2SbO6——Layered oxide cathode material. Example 2
[0018] This embodiment 2 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from that of embodiment 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0428 g of CuO, 0.01445 g of MgO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h, pour the resulting powder into the mold of the tablet press, place the mold under the tablet press, and compress it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Mg 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 F 0.05 @Cu3Mg2SbO6——Layered oxide cathode material. Example 3
[0019] This embodiment 3 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from that of embodiment 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0428 g of CuO, 0.0292 g of ZnO and 0.0418 g of Bi2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of a tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Cu 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Bi 0.02 O 1.95 F 0.05 @Cu3Zn2BiO6——Layered oxide cathode material. Example 4
[0020] Example 4 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from Example 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0428 g of CuO, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add anhydrous ethanol directly and ball mill for 6 h, with a solid-to-material ratio of 10:1. Vacuum dry for 12 h, pour the obtained powder into the mold of the tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 F 0.05 @Cu3Zn2SbO6——Layered oxide cathode material. Example 5
[0021] Example 5 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from Example 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0262 g of NaCl, 0.0428 g of CuO, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of a tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 Cl 0.05 @Cu3Zn2SbO6——Layered oxide cathode material. Example 6
[0022] This embodiment 6 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from that of embodiment 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0350 g of Na2S, 0.0428 g of CuO, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of the tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 S 0.05 @Cu3Zn2SbO6——Layered oxide cathode material. Example 7
[0023] Example 7 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from Example 1 in that: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0199 g of Li2CO3, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of a tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 S 0.05 @Li3Zn2SbO6——Layered oxide cathode material. Example 8
[0024] Example 8 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping, which differs from Example 1 in that: S1. Weigh 0.5181 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, 0.2599 g of MnO2, 0.0188 g of NaF, 0.0292 g of ZnO and 0.0262 g of Sb2O3, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol as a dispersant and mix for 6 h. The solid-to-material ratio is 10:1. Vacuum dry for 12 h. Pour the resulting powder into the mold of the tablet press, place the mold under the tablet press, and press it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Na is obtained 0.98 Zn 0.02 Ni 0.32 Fe 0.32 Mn 0.34 Sb 0.02 O 1.95 S 0.05 @Na3Zn2SbO6——Layered oxide cathode material. Example 9
[0025] This embodiment 9 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and multi-site doping. The difference from embodiment 1 is that the ball milling mixing time in step S1 is 15 h. Example 10
[0026] This embodiment 10 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and multi-site doping. The difference from embodiment 1 is that the ratio of ball milling beads to cathode material in step S1 is 15:1. Example 11
[0027] This embodiment 11 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and synergistic multi-site doping. The difference from embodiment 1 is that, in step S2 sintering, the heating and cooling rates are both 5%. o C / min. Example 12
[0028] This embodiment 12 provides a method for preparing a layered oxide cathode material for sodium-ion batteries with honeycomb layered coating and multi-site doping. The difference from embodiment 1 is that the sintering atmosphere in step S2 is air.
[0029] Comparative Example 1 This embodiment 1 provides a method for preparing a layered oxide cathode material for sodium-ion batteries, including the following steps: S1. Weigh 0.4896 g (sodium ratio 1:1.03) of Na2CO3, 0.2233 g of NiO, 0.2387 g of Fe2O3, and 0.2599 g of MnO2, mix and grind them together. During the mixing process, add 3 ml of anhydrous ethanol and ball mill for 6 h, with a solid-to-material ratio of 10:1. Vacuum dry the mixture for 12 h, pour the resulting powder into the mold of a tablet press, place the mold under the tablet press, and compress it into tablets at a pressure of 10 MPa for 20 min to obtain the mixed material. S2, Preparation of NaNi 0.33 Fe 0.33 Mn 0.33 O2 — Layered oxide cathode material.
[0030] Performance testing The positive electrode materials prepared in Example 1 and Comparative Example 1 were thoroughly mixed with polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, and then uniformly coated onto aluminum foil, with the areal density controlled at 1.5~2.5 mg / cm³. 2 After drying in a vacuum drying oven at 100℃, the electrodes were cut into circular positive electrode sheets with a diameter of 12mm. Using sodium metal sheets as the positive electrode sheets, Whatman Grade GF / D type glass fiber as the separator, and NaClO4 / diethyl carbonate (EC:DEC) solution as the electrolyte, they were assembled into 2032 type coin cells in an argon glove box. Electrochemical performance tests were conducted at 25℃. A comparison of the X-ray diffraction patterns of Example 1 and Comparative Example 1 is shown below. Figure 1 As shown in the figure, the comparison graph of the 0.1C first-cycle charge-discharge curves of Example 1 and Comparative Example 1 is as follows. Figure 2 As shown, the cycling performance of Example 1 and Comparative Example 1 is as follows: Figure 3 As shown.
[0031] from Figure 1 It can be seen that the XRD diffraction patterns of both the examples and the comparative examples can be indexed to the O3 phase layered structure. However, after amplifying the (003) and (104) characteristic peaks, it was found that the (003) peak and (104) peak of the examples shifted significantly to a lower angle. This is attributed to the doping of the three sites extending the C-axis and reducing the energy barrier during the diffusion of sodium ions.
[0032] from Figure 2As can be seen, the examples and comparative examples have similar curve shapes. The comparative example shows a long plateau around 4.1V, while in the examples, this long plateau is significantly suppressed. This can be attributed to the fact that the coating-coordinated multi-site doping alters the chemical environment around oxygen, allowing oxygen to remain stable even under high voltage, further demonstrating the high stability of the layered structure in the examples. Furthermore, the initial coulombic efficiency in the examples (91.24%) is significantly higher than that in the examples (85.88%).
[0033] from Figure 3 As can be seen, under a voltage range of 2-4.2 V and a current density of 1C, after 100 charge-discharge cycles, the cathode material prepared in the example has a capacity retention rate of 71.75%, which is higher than the 53.67% capacity retention rate of the cathode material prepared in the comparative example. This indicates that the coating-coated synergistic multi-site doping can make the transition metal layered oxide cathode material of sodium-ion battery have better cycle stability.
[0034] In summary, the stability and practicality of the sodium-ion battery cathode material with honeycomb layered coating and multi-site doping described in this invention are greatly improved. The preparation process of the cathode material has the advantages of readily available raw materials, simple preparation method, and high controllability, and has good application prospects.
[0035] While embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations fall within the scope and spirit of the invention as set forth in the claims. Furthermore, the invention described herein may have other embodiments and can be implemented or carried out in various ways.
Claims
1. A sodium-ion battery cathode material with honeycomb layered coating and synergistic multi-site doping, characterized in that: The positive electrode material has the general chemical formula Na. x-m B m (Ni a Fe b Mn 1-a-b ) 1-n C n O 2-y M y @A3B2CO6; where 0.66≤x≤1, 0≤a≤0.33, 0≤b≤0.33, 0≤y≤0.1, 0.05≤m≤0.2, 0.05≤n≤0.2, and A3B2CO6 is a honeycomb layered structure. The surface is modified while the M element is combined to achieve multi-site regulation.
2. The sodium-ion battery cathode material with honeycomb layered coating and synergistic multi-site doping according to claim 1, wherein M is selected from one of F, Cl, and S, and replaces oxygen ion sites to form strong TM-M bonds.
3. The sodium-ion battery cathode material with honeycomb layered coating and synergistic multi-site doping according to claim 1, wherein in A3B2CO6, A is selected from one of Na, Li, Cu, and Ag, B is selected from one of Zn and Mg, and C is selected from one of Sb and Bi, and the A3B2CO6 and Na x Ni a Fe b Mn 1-a-b O 2-y M y The mass ratio is (0.5% : 1) ~ (10% : 1).
4. The method for preparing the sodium-ion battery cathode material with honeycomb layered coating and synergistic multi-site doping as described in any one of claims 1 to 3, characterized in that, include: (1) Add sodium source, nickel source, iron source, manganese source, compound M, compound A, compound B and compound C into a ball mill jar, and then select appropriate solvent, rotation speed, ball milling time and solid ratio for ball milling and mixing. After ball milling, transfer to a vacuum drying oven for drying. (2) The obtained powder sample is pressed into tablets under a certain pressure and then sintered under a certain sintering atmosphere. After the reaction is completed, a sodium-ion battery cathode material with honeycomb layered coating and multi-site doping is obtained.
5. The method for preparing the honeycomb layered coated sodium-ion battery cathode material with synergistic multi-site doping according to claim 4, characterized in that, In step (1), the nickel source, manganese source, and iron source are one or more of their corresponding oxides, acetates, chlorides, nitrates, and sulfates; the sodium source includes one or more of Na2CO3, NaNO3, and NaHCO3. Compound M includes one or more of acetate, ammonium salt, and sodium salt; Compound A includes one or more of the following: oxides, nitrates, acetates, carbonates, and hydroxides; Compound B includes one or more of oxides, nitrates, acetates, carbonates, and hydroxides; Compound C includes one or more of oxides, nitrates, acetates, carbonates, and hydroxides; The ball milling solvent includes any one of methanol, ethanol, propanol, and diethyl ether; the mass ratio of the ball milling beads to the material is 10-15:1; The ball milling time is 6~15 h, the rotation speed is 400~800 r / min, and the vacuum drying time is 12~20 h.
6. The method for preparing the honeycomb layered coated sodium-ion battery cathode material with synergistic multi-site doping according to claim 4, characterized in that, In step (2), the sintering atmosphere is one or more of oxygen or air; the sintering method is one or more of microwave sintering, atmospheric pressure sintering, hot pressing sintering, reaction sintering, and self-sintering; and the pressing pressure is 0.5 MPa to 10 MPa. The sintering time is 12-20 h, the heating rate is 2-5 degrees per minute, and the sintering temperature is 850-950℃.